Proteomic analysis of liver on high fat diet mice treated with Toona Sinesis (Meliaceae) leaf extract - Ly, Ta Ngoc; Joan, Chang Sue (Vietnam Journal of Science and Technology, 2015)
The major pathogenesis of metabolic syndrome is the development of insulin resistance, which promotes the elevation of blood pressure, dyslipidemia, and dysregulation of glucose metabolism. Liver is the principal regulator of glucose and lipid metabolism by controlling hepatic glucose production, glycogen storage and lipogenesis. Toona sinnesis (TS) has been reported to be beneficial on health metabolic syndrome, however the effects of TS on liver metabolism is not clear. TS leaves extract (TSL-E) in relation to glucose and lipid metabolism in liver was studied in high fat diet model that induced insulin resistance by feeding the mice with high fat diet for 8 weeks followed by treatment of TSL-E (100mg/kg body weight) for 4 weeks. Two-dimensional gel electrophoresis followed by mass spectrometry was carried out to identify differential expression of liver proteins. In addition, western blot and real time PCR were performed for validation of proteomic analysis. Up-regulated expression of genes involved in b-oxidation (PPARa and ACO) was observed in liver of TSL-E treated mice. In contract, down-regulated expression of genes was involved in lipogenesis (ACC), lipids transport (L-FABP) and decreased expression of proteins was involved in gluconeogenesis (Transaldolase, Enolase, PCK2 and Nudix). In conclusion, Toona sinnesis mediates its anti-metabolic syndrome potential through improvement of dyslipidemia and blood glucose by promoting b-oxidation and inhibiting gluconeogenesis, lipogenesis and glycogen synthesis